High-Score US-Suspicious Subcentimeter Thyroid Nodules: What Factors Affect Adequate Sampling of US-Guided Fine-Needle Aspiration Biopsy? - Yang Li; Jin Hong Yu; Ping Jie Du; Yu Xie; Sushant Kumar Das; Bing Li; Chuan Zhang (International Journal of Endocrinology)
Background. Fine-needle aspiration biopsy (FNAB) is diagnostic standard for thyroid nodules. However, the influence of adequate sample rate of US-guided FNAB for subcentimeter thyroid nodules is not known well. Objectives. To assess the factors affecting adequate sample rate of US-guided FNAB for subcentimeter thyroid nodules. Methods. Three hundred and forty-nine consecutive US-guided FNAB procedures were performed in 344 patients with subcentimeter thyroid nodules. The adequate sample rate was analyzed for all nodules on the basis of nodule-related and technical factors. The factors affecting adequate sample rate of US-guided FNAB for subcentimeter thyroid nodules were determined by multivariate logistic regression. Results. The adequate sample rate increased with larger nodules (72.7% for 3–6 mm nodules and 84.9% for 7–10 mm nodules (P=0.007)). The adequate sample rate was 63.9%, 81.3%, and 90.6% in nodules with macrocalcifcation, microcalcification, and no calcification, respectively (P<0.001). The adequate sample rate was 71.8% for biopsies performed with a perpendicular needle path and 85.0% with a parallel needle path (P=0.004). The significant factors affecting adequate sample rate of US-guided FNAB for subcentimeter thyroid nodules were nodule size (P<0.001; odds ratio (OR) for 7–10 mm nodules was approximately 3.0 times higher than that for 3–6 mm nodules), calcification (P<0.001; OR for nodules without calcification was approximately 5.3 times higher than that for the nodules with macrocalcification), and needle path (P=0.044; OR for the use of the parallel needle path was about 1.8 times higher than that for the perpendicular needle path). Conclusion. Nodule size, calcification, and needle path were the determinants of sample adequacy. The adequate sample rate was higher in larger nodules, in nodules without calcification, and upon using a parallel needle path for biopsy.